Pengaruh Harga, Word Of Mouth, Labelisasi Halal Terhadap Keputusan Pembelian Sabana Fried Chicken Di Bekasi - Elisa Nabila Putri; Hadita Hadita (JURNAL RISET MANAJEMEN (JURMA), 2024)
The purpose of this study was to determine the effect of Price, Word Of Mouth, Halal Labeling on Purchasing Decisions of Sabana Fried Chicken in Bekasi. The quantitative analysis assessment method is through primary data generated from distributing questionnaires online. The population in this study is the Bekasi community with a sample of 100 respondents. The data analysis techniques used in this study are Validity test, Reliability Test, Normality, Multiple Linear Regression Test, T Test (Hypothesis), F Test (Model Feasibility), Determination Coefficient Test. The results of the study partially the influence of Price has a positive and significant influence on purchasing decisions. partially the influence of Word Of Mouth has a positive and significant influence on purchasing decisions. partially the influence of Halal Labeling has a positive and significant influence on purchasing decisions. Simultaneously, it is known that Price, Word Of Mouth, Halal Labeling have a significant influence on purchasing decisions.